Lifelong learning community development: A case study of Thailand - Jarupisitthorn, Jirattha; Rattana-Ubol, Archanya; Kimpee, Parn (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research was to analyze the context of lifelong learning community development, a case study of three communities in Thailand, namely Puparn Royal Development Study Centre, Sakon Nakhon, Small and Micro Community Enterprise Doichang Macadamianut, Chiang Rai and Teacher Professional Learning Community at Satit Pattana School, Bangkok. This qualitative research employed a structured interview as a tool to collect data. The subjects of this study were 15 people who were the executives, the officers and the members of the mentioned lifelong learning communities. Collected data were analyzed using content analysis. The findings revealed that 1) the Main Goals of these communities arose from the needs to solve local problems which vary with the backgrounds of the communities, 2) the Community Members were internal personnel of the organizations and external people who liberally joined, 3) the Learning Process and Characteristics began from Local Problem Occurs to Collaborative Learning in order to find a solution, 4) Internal and External Support from members of the communities were the main factor to a successful operation, 5) Operation Evaluation was conducted by having meetings regularly to continuously analyze and follow-up on performance and 6) Building Lifelong Learning Community Network was emphasized due to the benefit of knowledge development, good practice sharing as well as the strength enhancement of a lifelong learning community.